2017
DOI: 10.3389/fpsyg.2017.00146
|View full text |Cite
|
Sign up to set email alerts
|

A Nuanced Look at Women in STEM Fields at Two-Year Colleges: Factors That Shape Female Students' Transfer Intent

Abstract: In this study, we explored the relationship between the intent to transfer upward and a set of motivational, contextual, and socio-demographic background factors among 696 female students beginning in science, technology, engineering, and mathematics (STEM) programs or courses at two-year colleges in a Midwestern state. Drawing upon survey data and administrative records, our multinomial logistic regression analysis revealed that students' math and science self-efficacy beliefs, as well as transfer-oriented in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 62 publications
1
24
0
Order By: Relevance
“…We found that SCCT extends to community college women in STEM and reinforces the importance of self‐efficacy (Wang, Chan, Soffa, & Nachman, ). Specifically, self‐efficacy in math and science is key to transfer in STEM (Wang, Chan, et al., ). Moreover, the model was extended in the sense that academic interests and concerns around future careers may play a larger role than self‐efficacy for two‐year college women.…”
Section: Conceptualizing Community College Women's Experiences and Pasupporting
confidence: 75%
See 3 more Smart Citations
“…We found that SCCT extends to community college women in STEM and reinforces the importance of self‐efficacy (Wang, Chan, Soffa, & Nachman, ). Specifically, self‐efficacy in math and science is key to transfer in STEM (Wang, Chan, et al., ). Moreover, the model was extended in the sense that academic interests and concerns around future careers may play a larger role than self‐efficacy for two‐year college women.…”
Section: Conceptualizing Community College Women's Experiences and Pasupporting
confidence: 75%
“…One framework was social cognitive career theory (SCCT; Bandura, 1986;Lent, Brown, & Hackett, 1994, 2000, which has been applied to the community college STEM context (Wang, 2013). We found that SCCT extends to community college women in STEM and reinforces the importance of self-efficacy (Wang, Chan, Soffa, & Nachman, 2017). Specifically, self-efficacy in math and science is key to transfer in STEM (Wang, Chan, et al, 2017).…”
Section: Conceptualizing Community College Women's Experiences and Pamentioning
confidence: 94%
See 2 more Smart Citations
“…The success of the academic adjustment of STEM students to a 4-year institution is influenced by previous experiences with faculty and staff (Bohanna 2016;Zamudio 2015), interactions with advisors (Jorstad 2015), exposure to role models and mentors (Edwards 2015), the intent to transfer (Wang et al 2017), support systems (Jackson 2013), and the overall experience of the transfer process (Jackson 2010). Students may face setbacks in the transfer process due to dissatisfactory advising or imperfect program alignment with the courses they have already taken (Packard, Gagnon, and Senas 2012).…”
Section: Two-year Transfersmentioning
confidence: 99%